2010
DOI: 10.1103/physrevb.81.184401
|View full text |Cite
|
Sign up to set email alerts
|

Detailed relationship between local structure, polarons, and magnetization forLa1xCaxMnO3

Abstract: We present detailed local structure measurements ͑using the extended x-ray absorption fine structure tech-nique͒ for the colossal magnetoresistive material La 1−x Ca x MnO 3 ͑0.21Ͻ x Ͻ 0.45͒ as a function of temperature and magnetic field. The local distortions of the Mn-O bonds are parameterized using , the width of the Mn-O pair-distribution function ͑PDF͒. After subtracting thermal phonon contributions, we show that the contributions to 2 from polaron and Jahn-Teller ͑JT͒ distortions, JT/polaron 2 , are a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 61 publications
(99 reference statements)
4
20
1
1
Order By: Relevance
“…showing the same trend in the modification of the width of the pair-distribution function (σ 2 ) and of the interatomic distances. 51 On the contrary, our results indicate that the next-neighbor Cu environment is similar in all the samples. The sintering temperature affects the disorder of further coordination shells lying in the plane perpendicular to the O-Cu-O bond.…”
Section: B Cu K -Edge X-ray Absorption Spectroscopycontrasting
confidence: 55%
“…showing the same trend in the modification of the width of the pair-distribution function (σ 2 ) and of the interatomic distances. 51 On the contrary, our results indicate that the next-neighbor Cu environment is similar in all the samples. The sintering temperature affects the disorder of further coordination shells lying in the plane perpendicular to the O-Cu-O bond.…”
Section: B Cu K -Edge X-ray Absorption Spectroscopycontrasting
confidence: 55%
“…Table 1 shows the fitting results of Cu K edge EXAFS spectra that correspond to the first coordination shell (Cu O). As can be observed, the Cu O mean bond length of both samples obtained from EXAFS results are similar to the literature obtained from XRD measurements [34]. The difference observed in the intensity of first peak of FT intensity between the two samples is due to the high degree of disorder (Debye-Waller factor ( )) in the CuAlO 2 compared to the Cu 2 O compound.…”
Section: X-ray Absorption Spectroscopy Of Cualo 2 Microspheressupporting
confidence: 86%
“…Later Lynn et al demonstrated the existence of a polaron glass phase characterized by short-range polaron correlations, present above T C [16]. In 2008, de Souza et al [17] suggested that the Griffiths-like treatment is inappropriate and a proper description should incorporate the formation of magnetic polarons (manifest as ferromagnetic clusters organized in Mn-spin dimers [18]) coalescing over the temperature range between T * and T C . In order to shed light on the origin of the ordering temperature T * , we have performed a detailed study comparing the magnetic, electronic, and structural properties of La 0.7 Ca 0.3 MnO 3 (orthorhombic LCMO) and La 0.7 Ba 0.3 MnO 3 (rhombohedral LBMO).…”
Section: Introductionmentioning
confidence: 99%